Socio-Economic Profile of the Union Members in APSRTC:A Case Study of Visakhapatnam City - Lydia, R.; Kumar, B. Ravi (American International Journal of Social Science Research, 2018)
Trade unions help in accelerated pace of economic development in many ways. They are helping in the recruitment and selection of workers, inculcating discipline among the workforce, enabling settlement of industrial disputes in a rational manner and helping social adjustments with their activities. Workers have to adjust themselves to the new working conditions, the new rules and policies. Workers coming from different backgrounds may become disorganized, unsatisfied and frustrated. Unions will help them in such adjustment. The present study is an attempt to portray the socio-economic-profile of the sample respondents (union members) with reference to Visakhapatnam City.